2017
DOI: 10.1002/hbm.23717
|View full text |Cite
|
Sign up to set email alerts
|

The independent influences of age and education on functional brain networks and cognition in healthy older adults

Abstract: Healthy aging is accompanied by a constellation of changes in cognitive processes and alterations in functional brain networks. The relationships between brain networks and cognition during aging in later life are moderated by demographic and environmental factors, such as prior education, in a poorly understood manner. Using multivariate analyses, we identified three latent patterns (or modes) linking resting-state functional connectivity to demographic and cognitive measures in 101 cognitively normal elders.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 151 publications
4
31
0
Order By: Relevance
“…Several studies have utilized CCA to study inter-correlations between behavioral data, cognition, imaging findings, and daily activity in both healthy subjects and disease populations ( 18 , 23 27 ), indicating that CCA is a useful tool to study relations between two sets of data. In PD, a CCA approach found that working memory, attention, planning, and problem solving were inter-correlated with visuospatial memory and episodic memory in early stage PD and executive function (index of working memory, attention, planning) and visuospatial memory contributed the most to cognitive deficits ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have utilized CCA to study inter-correlations between behavioral data, cognition, imaging findings, and daily activity in both healthy subjects and disease populations ( 18 , 23 27 ), indicating that CCA is a useful tool to study relations between two sets of data. In PD, a CCA approach found that working memory, attention, planning, and problem solving were inter-correlated with visuospatial memory and episodic memory in early stage PD and executive function (index of working memory, attention, planning) and visuospatial memory contributed the most to cognitive deficits ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…A further potential confound could arise from insufficient matching of participants according to intellectual achievement, 39 partially mitigated by reliance on spouses volunteering for inclusion as healthy controls. Finally, CNS active medications have the potential to accentuate the group difference in FC.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the main effect of education on FC was only detected in RS, as well as a significant interaction between age and education on fronto-parietal FC. Education level might in fact critically influence the brain's ability to use more specialized functional networks (Marques et al, 2016) and was reported to associate with increases in bilateral frontoparietal connectivity (Arenaza-Urquijo, 2013;Perry et al, 2017). The lack of significant age-education interaction on FC during vocabulary tasks remains hard to interpret and warrants further exploration using tasks drawn from a variety of cognitive contexts.…”
Section: The Association Between Performance Cognitive Reserve Estimmentioning
confidence: 99%